Implementasi Projek Penguatan Profil Pelajar Pancasila Melalui Program Reduce, Reuse, Recycle (3R) Menumbuhkan Karakter Peduli lingkungan dan Tangung Jawab - Maharani, Tidi; Reflesia, Citra (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Indonesia is in second place as the largest producer of plastic waste in the world. This condition, in conjunction with the various natural disasters that have occurred, emphasizes the need for character education for Indonesian society. The reduce, reuse, recycle (3R) program is one method to foster an environmentally caring attitude and a sense of responsibility in students, in order to create a clean and comfortable environment. This research aims to shape the character of students according to the Pancasila student profile, such as concern for the environment and a sense of responsibility, through school innovation as an effective learning tool. The method used in this research is descriptive with a qualitative approach. Research findings show that the implementation of the 3R program at SDN 17 Lubuklinggau has succeeded in forming a character that cares about the environment and a sense of responsibility. This effort is carried out by familiarizing students with separating waste based on its type, namely organic and inorganic waste. Apart from that, character formation is also carried out through daily habits, educational examples, cultivating discipline, integration in lessons, routine school activities, and structuring the learning environment.